Integrating acting techniques in informal learning for prospective primary teachers - Lyuft, Alexey; Akpayeva, Assel; Astambayeva, Zhupat; Kulgildinova, Tulebike (International Journal of Evaluation and Research in Education (IJERE), 2025)
The topic of informal education is particularly pertinent within the pedagogical science and practice of universities in Kazakhstan. Contemporary professional education emphasizes the importance of not only pedagogical skills but also the acting abilities of teachers. However, the development of acting skills among prospective primary teachers is generally underemphasized. This neglect is evident in the absence of relevant courses within the educational programs of Kazakhstani universities, as well as in the disproportionate emphasis on independent work over classroom and extracurricular activities related to acting and pedagogical techniques. This study aims to examine the benefits and applications of incorporating acting techniques into the training of prospective primary teachers to improve their professional preparation, support their ongoing professional development, and foster successful educational practice. The research findings revealed that specialized vocational preparation techniques are essential for the training of modern educators. This study found the impact of acting techniques on the educational process for preparing teacher candidates improved their professional preparation, while also supporting their ongoing professional development and fostering successful educational practice.